Pengembangan E- modul Flip PDF Materi Persamaan Nilai dan Vektor Eigen, serta Nilai Harap - Nada, Hairul; Purwaningsih, Sri; Pujaningsih, Febri Berthalita (UNIVERSITAS INDRAPRASTA PGRI, 2024)
AbstractThe Flip PDF Professional-assisted e-module is a digital electronic module developed with the help of the Flip PDF application. This e-module can assist students in need of effective learning media. This research aims to develop an e-module according to the ADDIE model, test the feasibility of the e-module in terms of media and content, and evaluate students' assessments of the e-module. The research was conducted at a university in September for the 2024/2025 academic year. Data were obtained through content and media validation questionnaires and student response questionnaires. This research used a Research and Development (R&D) method, with the development model following ADDIE (Analyze, Design, Develop, Implement, and Evaluate). The sampling method used was Random Sampling, involving 62 Physics Education students from Jambi University. The results from content and media experts showed that the Quantum Physics e-module developed with the help of Flip PDF Professional is feasible for testing. The student response questionnaire showed good statistics. The content feasibility aspect received a score of 78.81%, language aspect 79.35%, usability aspect 78.96%, and graphical aspect 79.48%. Therefore, it can be concluded that the Quantum Physics e-module product falls within the